Model of Consumer Protection in a Community - Hongchayangkool, Kullatat; Sutheeravut, Pongthep; Sukmak, Phen; Suwanchatree, Wanna; Ramtong, Jindawan; Chaingarm, Montha; Bulad, Lalita; Vimalai, Dacha (Health Science Journal of Thailand, 2024)
The action research developing a model of consumer protection in the community collected data from 108 participants, including consumers, entrepreneurs, executives, and workers of local authorities, and non-government organizations, using group discussions, in-depth interviews, and the operational feasibility questionnaire. The consumer protection model consisted of: 1) consumer protection management within the community by the volunteer groups; 2) consumer protection system management composing of policy, plans, budget, monitoring and evaluation, and representatives of volunteers in the sub-committee; 3) management of collaboration among partners; 4) creation of knowledge for sustainability; and 5) creation of the understanding process for the implementation. 64.52% of the participants were satisfied with the model’s design at a high level. The samples thought that the model serves the consumers’ needs (87.10%), influences on the entrepreneurs (61.29%), affects the structure and operation of the municipality (19.35%), and is adaptable (87.10%). Moreover, the sample also thought the municipality had a sufficient number of staff (54.84%), the staff are knowledgeable (80.65%) but not specialized, and the volunteers help transfer the knowledge thoroughly with empowerment. However, there should be knowledge creation about the protection for the subcommittee, staff, entrepreneurs, and consumers.